Respuesta :

Answer:

[tex]y=-\frac{x}{6} -1[/tex]

Step-by-step explanation:

Hi there!

We are given the following equation:
x+6y=-6

And we want to convert it into slope-intercept form

Slope-intercept form is known as y=mx+b, where m is the slope and b is the y intercept

The equation is currently in standard form, which is ax+by=c, where a, b, and c are integer coefficients

Notice how in standard form, both the terms that contain x and y are on one side, but in slope-intercept form, y is by itself on one side

So essentially, in order to convert from standard form to slope-intercept form, we need to solve for y

Here is our equation again:

x+6y=-6

Start by subtracting x from both sides

x+6y=-6

-x       -x

_______________

6y=-x-6

Now divide both sides by 6

[tex]y=-\frac{x}{6} -\frac{6}{6}[/tex]
We can simplify the fractions to become:

[tex]y=-\frac{x}{6} -1[/tex]
Hope this helps!

See more on converting from standard to slope-intercept form here: https://brainly.com/question/26579052